Efficiency of Multiple Extraction Solvents on Antioxidant, Cytotoxic, and Phytotoxic Potential of Taraxacum officinale (L.) Weber ex F.H. Wigg. from Poonch Valley, Azad Kashmir, Pakistan. (24th May 2022) - Akhtar, Wasim; Ali, Ghazanfar; Ashraf, Nadia; Fatima, Iram; Kayani, Waqas Khan; Shaheen, Hamayun; Ghoneim, Mohammed M.; Abdelgawad, Mohamed A.; Khames, Ahmed
Abstract : Background . Different parts of Taraxacum officinale (L.) were used in traditional medicine in various parts of the world for the treatment of health problems, and they possess significant biological activities. The present study aimed to estimate phytochemical and biological activities of T. officinale using different extraction solvents. Methods . Methanolic, acetone, and n-hexane extracts of selected species were prepared, and ten secondary metabolites were examined using standard protocols. The antioxidant activity was performed using three in vitro methods, namely, DPPH assay, total reducing power (TRP) assay, and total antioxidant capacity (TAC). Toxicological analysis was done using the brine shrimp cytotoxic assay and radish seed phytotoxic assay. Results . The T. officinale methanolic extract showed the highest phenolic (178.27 ± 17.17 mg/GAE/g) and flavonoid (18.50 ± 1.64 mg QE/g) contents. Similarly, the methanolic extract also revealed the highest DPPH activity (32.80 ± 9.66 IC50 ), reducing potential (0.53 ± 0.02 mg/g), and TAC (19.42 ± 0.97 mg/g) as compared to the acetone and n-hexane extracts. The Pearson correlation analysis confirmed a strong positive correlation ( r > 0.9) between total phenolic content (TPC), total flavonoid content (TFC), and all antioxidant assays. Furthermore, a heat map displayed the methanolic extract (red color) as a valuable source of phytochemicals and antioxidant agents. Moreover, the T. officinale methanolic extract also showed the highest (7.12 ppm) cytotoxic potential whereas both methanolic and acetone extracts were revealed as moderate phytotoxic agents when compared with the standard. Conclusion . The T. officinale methanolic extract exhibited comparatively notable phytochemicals that are actively involved in antioxidant activities and possess toxicological properties. This upholds the folkloric use of T. officinale as a possible source to develop natural plant-based drugs. Further investigations to isolate bioactive compounds and elements and on their safety need to be conducted.